A sacramental life : a festschrift honoring Bernard Cooke - Cooke, Bernard J., 1922-; Barnes, Michael Horace; Roberts, William P., 1931- (Marquette studies in theology, 2003)
"The authors of this volume have explored diverse aspects of Bernard's major theological focus, drawn from them, and directly and indirectly addressed them in a variety of topics."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved